PENGARUH RETRIBUSI TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN BOLAANG MONGONDOW SELATAN - Arlin Nadjamudin; Irawati Abdul; Sudirman (Yayasan Pendidikan Sudirman Mandiri, 2025)
The research aimed to determine the influence of retribution on Regional Original Revenue in Bolaang Mongondow Selatan Regency. This study used a quantitative approach with the ex-post facto method. The data used were primary data obtained from distributing questionnaires to the people paying the retribution and amployees of the BPKPD (Financial Management and Regional Revenue Agency) of Bolaang Mongondow Selatan Regency. The samples were 38 respondents. Data analysis used simple linear regression. The results showed that there was an influence of retribution on Regional Original Revenue. The influence of retribution on the Regional Original Revenue was 26,6%, while the remaining 73,4% was influenced by variables not examined.